Spain, La Roja, and the forging of the nation: truth or fiction? - Kubiaczyk, Filip (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper analyzes the role of the national team of Spain denoted by the neologism La Roja in promoting patriotic sentiments and building national unity. In a 2014 study entitled Goles y banderas. Fútbol e identidades nacionales en Espa?a, Alejandro Quiroga Fernández de Soto argues that the successes of the team in 2008-2012 (Champions of Europe in Austria and Switzerland, World Champions in South Africa and again Champions of Europe in Poland and Ukraine), brought about a patriotic revival, while La Roja itself became an integrating factor which united the Spanish regardless of political differences and distinct identities.
Keywords: football; La Roja; Spain; Spanish national team; Catalonia; Basque Country; nationalism; patriotism; national unity